The Correlation between Students’ Anxiety and Speaking Performance at The Second Grade In SMAN 1 Pantai Cermin Kabupaten Solok in Academic Years 2019/2020 - Oktavia, Peni; Syahrul, Syahrul (Faculty of Education and Teacher Training of IAIN Palopo, 2021)
ABSTRACT The background of this research was the presence of anxiety among some students in their English Speaking activities in the school. In language learning, anxiety influenced speaking performance. Therefore, the researcher conducted observations and interviews to finding the real condition. In addition, some students had anxieties when speaking English because anxiety had an effect on performance while some other students had no problems. Relate to this condition, the researcher wanted to investigate the correlation between students’ anxiety and speaking performance at the second grade of SMAN 1 Pantai Cermin Kabupaten Solok Academic years 2020/2021. This research used quantitative approach in the type of the correlation design. The population of this research was all class of the second grade in SMAN 1 Pantai Cermin and all of them became sample because they were less than hundred. The data was got by questionnaire and documentation. The students fill the questionnaires directly relate to their anxiety in speaking. The questionnaires was adopted and adapted from foreign language classroom anxiety scale (FLCAS) developed by Horwitz (1986). The data of the documentation were taken from the students’ final scores in the speaking.To analyze the data, the researcher used the SPSS version 20 for windows. In analyzing the data, the researcher used Person Product Moment formula to find out the significant correlation, to find out the correlation direction and to find out the correlation magnitude of students’ anxiety and speaking performance. The results of the research showed that there was a correlation between students’ anxiety and speaking performance at the second grade of SMAN 1 Pantai Cermin academic years 2019/2020. The researcher found that the coefficient of correlation between students’ anxiety and speaking performance at the second grade of SMAN 1 Pantai Cermin was 0,146. The correlation was positive and significant. It means that Ho is rejected and Ha is accepted. Thus, there is a positive correlation between students’ anxiety and speaking performance at the second grade of SMAN 1 Pantai Cermin. Based on the result of the research, it can be conclude that if the students have high anxiety automatically she/he have low ability in speaking performance or when the students have low anxiety automatically she/he have high ability in speaking performance.